Assessment of the soil chemical properties on the intensive coffee plantations in the Central Highlands, Vietnam - Ky, Nguyen Vu; Trung, Ta Hoang; Anh, Pham Lan; Long, Hoang Hai; Truc, Dinh Thi Nha; Anh, Nguyen Huy (Brawijaya University, 2026)
The soil chemical properties in coffee-growing areas were important factors determining the growth, productivity, quality, and coffee flavour of Vietnam’s coffee. This study evaluated the soil chemical characteristics of intensive coffee lands in the four major coffee-producing provinces of the Central Highlands. A total of 1,095 soil samples were collected over a two-year period (from 2022 to 2023) within the coffee canopy to a depth of 30 cm for Robusta coffee. Chemical properties analyses were conducted at the Central Laboratory of the Western Highlands of Agriculture and Forestry Science Institute (WASI), focusing on five parameters: soil pH, organic matter, total nitrogen, available phosphorus, and available potassium. Results indicated that the coffee cultivation soils exhibited a high acidic pH value, with an average pH of 4.06. Organic matter content was generally high (4.25-5.40%), and total nitrogen fluctuated around the threshold of 0.19%. Available phosphorus was the most imbalanced nutrient, with excessive accumulation in Gia Lai, Dak Lak, and Lam Dong, while available potassium exhibited greater variability. Long-term monitoring (1994-2023) revealed a trend of gradual acidification over time under intensive coffee cultivation conditions. There was a significant accumulation of macronutrients, including total nitrogen, available phosphorus, and potassium, which raised signal inefficiencies in fertilizer management and increased risks of soil degradation and environmental pollution.